Analysis of chromosomal abnormalities in patients with hematological malignancies in Isfahan population - Hamid Ganji; Mansour Salehi; Alireza Moafi; Amin Izaditabar; Zakiye Nadeali; Mohamad Amin Honardost; Atefeh Baghersad; Akram Hashemian; Majid Hosseinzadeh (Fasa University of Medical Sciences, 2017)
Background & Objectives: Numerical and structural chromosomal abnormalities are known to be associated with predisposition to hematologic malignancies development and even different response to treatment. Both diagnostic and prognostic values of cytogenetic analysis of chromosome rearrangements are helpful for better therapeutic decision in management of hematologic malignancies. On the other hand, the study of chromosomal rearrangement in patients with leukemia has led to the identification of the relationship between chromosomal abnormalities and the prognosis of the disease. This study aimed at determining the incidence of structural and numerical chromosomal abnormalities in patients with hematologic malignancies and their correlation with prognostic factors. Material & methods: Cytogenetic analysis was performed on 59 bone marrow samples from patients who were referred to genetics laboratory of Alzahra University-Hospital of Isfahan Medical University. Results: Karyotype analysis of these 59 patients showed chromosomal abnormalities in 16 (27.1%) patients and the remaining 43 (72.8%) patients had normal karyotype. Conclusion: The results suggest that conventional karyotype analysis can be used as an effective method for diagnosis and prognosis in patients with hematological malignancies.